HIV-1 Nef inhibits the JAK/STAT signaling pathway by inducing proteasomal degradation of STAT1 - Roger L. Rodrigues; Mara E. da Silva-Januário; Vinicius B. Apolloni; Constanza E. Espada; Taissa R. Jorge; Lucas A. Tavares; Andreia N. de Carvalho; Juliano P. Souza; Eurico Arruda; Iranaia Assunção-Miranda; Daniel S. Mansur; Luis L. P. daSilva (PLoS ONE, 2026)
Type I interferon (IFN-I) is critical for controlling viral infections through the activation of the JAK/STAT signaling pathway, which drives the transcription of interferon-stimulated genes (ISGs) with diverse antiviral functions. Despite its importance, the effectiveness of IFN-I treatment against HIV-1 is limited. The HIV-1 accessory protein Nef is highly expressed early during infection and is detectable in the serum of HIV-1-infected individuals. Furthermore, Nef is a key factor in viral pathogenesis and disease progression, that has been shown to antagonize specific ISG products via post-translational mechanisms. To investigate if Nef plays a broader effect in antiviral responses, we used a T cell line constitutively expressing Nef and analyzed the JAK/STAT pathway activation after IFN stimuli. Here, we demonstrate that Nef interferes with the JAK/STAT signaling pathway by selectively depleting STAT1 in T cells. This Nef-mediated depletion depends on Nef myristylation and proteasomal activity but not on lysosomal activity. In contrast, the levels of STAT2, an interaction partner of STAT1, as well as the phosphorylation of upstream kinases JAK1 and TYK2, remain unaffected by Nef. Importantly, the depletion of STAT1 in Nef-expressing T cells compromises the induction of antiviral ISGs by IFN-α. These findings reveal a novel role for Nef in T cells, suggesting a mechanism through which HIV-1 evades IFN-α-induced antiviral responses, potentially contributing to viral immune evasion.